دور الأنشطة المدرسية في نشر الوعي الثقافي لدى التلاميذ - عاشور, سعيد; كبار, عبدالله (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة للتعرف على دور الأنشطة المدرسية في نشر الوعي لدى التلاميذ, وهذا بالنظر إلى الأهمية التي تكتسيها هذه الأنشطة ضمن الرؤية الحديثة للتربية , والقائمة على الاهتمام الشامل بجوانب حياة المتعلمين ولا سيما في الجوانب الثقافية, وهذا في ظل التطور المعرفي والتكنولوجي الذي عرفته المجتمعات و الذي بات يهدد ثقافتها وهويتها وبالتالي استقرارها, وهذا ما دفع بالعديد من الدول لإصلاح منظوماتها التربوية للتكيف مع هذه التغيرات, حيث تعتبر الأنشطة المدرسية واحدة من هذه الاصلاحات والبدائل, وللوصول إلى فهم أكثر لدور هذه الأنشطة اتخذت من المنهج الوصفي منهجا للدراسة، الذي فرض علينا استخدام الأساليب والأدوات التي يتطلبها مستعينا بالاستمارة، والملاحظة ، والتحليلات الإحصائية، من خلال عينة قصدية، وتوصلت الدراسة إلى أن النشاط المدرسي يعمل على استذماج قيم ومعايير المجتمع لدى التلاميذ ,كما يساعد الطلبة على امتلاك بعض المهارات في مجال التعبير والأسلوب, إضافة إلى توثيق العلاقات الاجتماعية من خلال إحياء بعض المناسبات الاجتماعية.Abstract: The study aimed to identify the role of school activities in spreading awareness among students, and this is in view of the importance of these activities within the modern vision of education, which is based on comprehensive interest in aspects of learners' lives, especially in cultural aspects, and this is in light of the knowledge and technological development that societies have known, which It threatens its culture, identity, and therefore its stability, and this prompted many countries to reform their educational systems to adapt to these changes, as school activities are considered one of these reforms and alternatives, and to reach a more understanding of the role of these activities, the descriptive approach was taken as a study method, which forced us to use methods And the tools that it requires, using the form, observation, and statistical analyzes, through an intentional sample, and the study concluded that the school activity works to elicit the values and standards of society among students, and also helps students to possess some skills in the field of expression and style, in addition to documenting social relations through Reviving some social events.
مقال
Keywords: دور ; أنشطة مدرسية ; نشر ; وعي ثقافي ; تلاميذ; role; school activities; spreading; cultural awareness; students